Effect of Ethanol Extract Karamunting Leaf (Rhodomyrtus Tomentosa (Aiton) Hassk) on Testosterone Hormone Levels of Diabetes Mellitus Model Rats - Husnul Khatimah; Lena Rosida; Siti Kaidah; Ida Yuliana (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2021)
Karamunting leaf is a natural ingredient in South Kalimantan and is used for the treatment of diabetes mellitus. Diabetes mellitus (DM) can decrease hormone testosterone. Research on Karamunting leaves on testosterone levels had not been widely studied. The aim was to analyse the effect of administration ethanol extract Karamunting leaf on testosterone levels in diabetic rats induced by streptozotocin. The method was true experimental, Posttest Control Group. The research groups were divided into 4 groups. The control group giving streptozotocin induction at dosage 40 mg/kg bw rats intra-peritoneally. The treatment group was a group of rats DM treated with ethanol extract of Karamunting leaf at dosage 100 mg/kg bw, 200 mg/kg bw, and 400 mg/kg bw. The treatment in the research group was carried out for 14 days. On day 15, blood was taken to measure testosterone levels by the ELISA method and glucose blood. The data were analysed with Kolmogorov Smirnov and Mann Whitney. Testosterone levels increased with administration of ethanol extract Karamunting leaves at dose 100 mg/kg bw (16.58 ± 2.8) and 400 mg/kg bw (16.17 ± 2.07) when compared with the control group (14.56 ± 0.8). Administration of ethanolic extract of Karamunting leaf in DM rats has an effect on testosterone levels.